2019
DOI: 10.1103/physrevb.100.165109
|View full text |Cite
|
Sign up to set email alerts
|

Local metallic and structural properties of the strongly correlated metal LaNiO3 using 8Li βNMR

Abstract: We report β-detected NMR of ion-implanted 8 Li in a single crystal and thin film of the strongly correlated metal LaNiO 3 . In both samples, spin-lattice relaxation measurements reveal two distinct local metallic environments, as is evident from T-linear Korringa 1/T 1 below 200 K with slopes comparable to other metals. A small, approximately temperature independent Knight shift of ∼74 ppm is observed, yielding a normalized Korringa product characteristic of substantial antiferromagnetic correlations, but, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 65 publications
2
14
0
Order By: Relevance
“…Biexponential relaxation appears intrinsic to 8 Li in LaNiO 3 , and a similar analysis was necessary for a bulk single crystal. 7 Interestingly, the fast relaxing fraction 𝑓 𝑓 = 50 % independent of LaNiO 3 thickness, and in agreement with the bulk. 7 For further details on the analysis, see the Supporting Information.…”
supporting
confidence: 66%
See 3 more Smart Citations
“…Biexponential relaxation appears intrinsic to 8 Li in LaNiO 3 , and a similar analysis was necessary for a bulk single crystal. 7 Interestingly, the fast relaxing fraction 𝑓 𝑓 = 50 % independent of LaNiO 3 thickness, and in agreement with the bulk. 7 For further details on the analysis, see the Supporting Information.…”
supporting
confidence: 66%
“…7 Interestingly, the fast relaxing fraction 𝑓 𝑓 = 50 % independent of LaNiO 3 thickness, and in agreement with the bulk. 7 For further details on the analysis, see the Supporting Information.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…Further, Mandal et al have demonstrated that the BD phase appears when the effective charge transfer energy becomes negative [42]. Surprisingly, signatures of breathing distortion have been also found in the metallic phase of LaNiO3 [43]. On the other hand, there are also reports emphasizing the importance of structural transition [44,45] and polaron condensation [46].…”
mentioning
confidence: 99%